Generation of Maxwell-displacement-current of Phospholipid Monolayers at the Air/Water Interface - Sulaiman, K.; Majid, W.H.A.; Muhamad, M.R. (2004)
A series of amphiphilic organic materials of phospholipids with different alkyl chain namely 1,2-dimyristoyl-sn-glycero-3-phosphatidylethanolamine (DMPE) 1,2-dipalmitoyl-sn-glycero-3-phosphatidylethanolamine (DPPE) and 1,2-disteroyl-sn-glycero-phosphatidylethanolamine (DSPE) have been studied as Langmuir monolayers on the water surface. The organization of the Langmuir monolayers have been investigated using Maxwell-Displacement-Current (MDC) measuring technique. The MDC studies can give very essential information on the orientational order of the organic monolayers even at immeasurably low surface pressure. The current is generated due orientational changes of polar molecules induced by the monolayer compression. The features of the first order phase transitions in the surface pressure-area isotherms of the phospholipids monolayer are discussed.